ChemInform Abstract: Synthesis, Characterization and Performance of Cd1‐xInxTe Compound for Solar Cell Applications. Issue 26 (6th June 2013) - Shenouda, Atef Y.; Rashad, Mohamed M.; Chow, Lee
Abstract Samples of the title compound with 0 ≤ x ≤ 1.0 are prepared by reaction of CdSO4, InCl3, and TeCl4 in aqueous NH3 solution (pH 9) followed by addition of NaBH4 solution (85 °C, 2 h) to reduce the formed hydroxide phase to the alloy.